(untitled) (Universal International Scientific Journal, 2026)
This article discusses the psychological and pedagogical foundations of the formation of motivation in children. It analyzes the concepts of intrinsic and extrinsic motivation, their role in the development of the child’s personality and their importance in the educational process. It also shows how parents and educators can create a positive motivational environment by arousing interest in children, teaching them to set goals, encouraging and supporting them. The article substantiates the fact that motivation is an important factor in developing independence, responsibility and self-confidence in children.